INFLUENCE OF FIBREGLASS MESH ON PHYSICAL PROPERTIES OF LIGHTWEIGHT FOAMCRETE - Mat Serudin, Anisah; Othuman Mydin, Md Azree; Abdul Ghani, Abdul Naser (IIUM Engineering Journal, 2020)
This research project was designed to investigate the influence of fibremesh on the durability properties of lightweight foamcrete (LFC). The fibremesh, categorized as a synthetic fibre (man-made fibre), was used for this study. It poses a continuous fibre with warp and weft structure that was used as confinement material in this investigation where four different weights per area (g/m2) of the fibremesh were observed namely, 110 g, 130 g, 145 g, and 160 g. Three experimental tests were involved in this preliminary study: porosity, water absorption, and drying shrinkage test. All the specimens were confined with 1-layer fibremesh at a constant density of 1100kg/m3 of LFC and the result was compared with the control (unconfined LFC). The 160 g/m2 of fibremesh significantly improved the physical properties of LFC where 13.8%, 20%, and 57.4% enhancement was obtained for the porosity, water absorption, and drying shrinkage result, respectively. ABSTRAK: Projek penyelidikan ini dijalankan bagi menyiasat kesan pengunaan jejaring sabut pada sifat ketahanan konkrit ringan berbusa (LFC). Jejaring sabut yang digunakan dalam kajian ini adalah jejaring gentian kaca tahan-alkali yang dikategorikan sebagai serat sintetik yang juga dikenali sebagai fabrik tekstil. Ia mempunyai serat yang panjang dan bersambung dengan struktur yang lekuk dan renda yang digunakan sebagai penambahbaikan bagi konkrit ringan berbusa. Terdapat empat berat jejaring sabut yang diuji iaitu 110 g, 130 g, 145 g, dan 160 g. Tiga jenis eksperimen bagi kajian awal ini iaitu keliangan, penyerapan air, dan pengecutan pengeringan. Semua spesimen dibalut dengan 1 lapisan jejaring sabut pada 1100kg/m3 LFC dan data yang diperoleh dibandingkan dengan spesimen yang tidak dibalut dengan gentian kaca berjejaring. Jejaring sabut 160 g/m2 meningkatkan sifat fizikal konkrit ringan berbusa di mana 13.8%, 20%, dan 57.4% peningkatan diperoleh bagi keliangan, penyerapan air, dan pengecutan pengeringan, masing-masing.